La pliometría en le remate de voleibol de la categoría pre-juvenil damas de la Federación Deportiva de Chimborazo en el año 2015. (2016). - Bonilla Oñate, Dennys Patricio (2016)
ABSTRACT: Plyometrics is a type of explosive training, it is the highest quality training in explosives motions. Plyometrics is a very effective strategy to gain strength, improve fitness. It is about resistance exercises, such as jumping, throwing a ball and swinging, to make the body to produce large amounts of power in very short periods of time. Involves jumping from a height and when they reach the ground make a jump quickly. The initial height varies according to the degree of training of the subject, age and level. You cannot make every day because it affects a lot at neuromuscular, it is very effective to increase the power. Plyometrics is a complement to the training of different sporting disciplines, which helps to improve significantly the athlete´s performance. The research paper entitled "plyometrics in the volleyball final hot for category pre youth pre ladies at the Chimborazo Sports Federation 2015" the main objective was to determine how plyometrics impact in the volleyball athletes final hit. The trainings were conducted between August and December 2015 in the FDCH and applied to all the 20 athlete. The observation technique was used in the research and a longitudinal jump as an instrument, vertical jump test and final hit test evaluation the same as those applied at the beginning and end of the investigation to determine how vas its influence. After we compared the results we conclude that through the plyometric training we improved, reach and maintain the levels of hopping tests of the athletes.